Digital Technology Adoption and Its Impact on Third-Party Logistics Service Providers in Tamil Nadu - Ruthramathi, R.; Sivakumar, V. (Indian Journal of Information Sources and Services, 2025)
The paper mainly focused on third-party logistics as the central part of the changes that have undergone quick development in digital technologies. It helps to improve service delivery and maintain competitiveness in changing markets to streamline operations. 3PL should provide TN, the center of manufacturing, trade, and logistics in India. This research study mainly explained that the 3PL services are provided to the TN used by digital technology. It also explored the various effects related to overall performance, cost reduction, and operational efficiency. These technologies impact cloud computing, big data analysis, warehouse automation, AI, and real-time tracking systems. The research findings are that digital technologies provide productivity to improve customer communications. Most digital platforms are enabled by delivering various services, such as response time, personalized solutions, and real-time tracking. Challenges include high implementation costs and data security. This research study mainly benefited from digital advancements. Digital technology adoption has various key factors, along with expansion and competitiveness among Tamil Nadu 3PLs.